DEVELOPING CRITICAL THINKING SKILLS THROUGH COLLABORATIVE SPEAKING ACTIVITIES - Nuriya Yelamanova, (PEDAGOGS, 2025)
Abstaract: Nowadays, in educational context, critical thinking has emerged as an essential skill for lifelong learning and effective communication. The improvement of this competence has become a vital pedagogical goal in English as a foreign language (EFL) classroom. This article explores the role of collaborative speaking activities in fostering critical thinking skills among university-level learners. Drawing on constructive and socio-cultural learning theories, the study shows the effectiveness of interactive speaking tasks, such as debates, problem-solving discussions, and project-based collaboration- in enhancing students’ analytical and reflective abilities. Also, the article presents insights from recent research, highlights pedagogical implications for EFL instructors, and provides practical recommendations for integrating collaborative speaking activities to promote critical thinking in language classroom.